2017
DOI: 10.1038/gt.2017.69
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the CXCR4/CXCL12 axis in treating epithelial ovarian cancer

Abstract: Ovarian carcinoma is the most crucial and difficult target for available therapeutic treatments among gynecological malignancies, and great efforts are required to find an effective solution. Molecular studies showed that the chemokine stromal cell-derived factor-1 (also known as CXCL12) and its receptor, CXCR4, are key determinants of tumor initiation, progression and metastasis in ovarian carcinomas. Hence, it is generally believed that blocking the CXCR4/CXCL12 pathway could serve as a potential therapy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…Therefore, small molecular antagonists targeting CXCR4, such as BKT140, plerixafor and AMD3100, have been widely used in cancer treatment. 13 In conclusion, we have firstly demonstrated the activation of adenosine A2A receptor inhibits the proliferation, migration and invasion ability of PC-9 cells in this research. We have revealed that adenosine A2A receptor modulates the lung-to-brain metastasis via regulating the tight junction protein levels to regulate the integrity and function of BBB.…”
Section: Parametersmentioning
confidence: 59%
See 2 more Smart Citations
“…Therefore, small molecular antagonists targeting CXCR4, such as BKT140, plerixafor and AMD3100, have been widely used in cancer treatment. 13 In conclusion, we have firstly demonstrated the activation of adenosine A2A receptor inhibits the proliferation, migration and invasion ability of PC-9 cells in this research. We have revealed that adenosine A2A receptor modulates the lung-to-brain metastasis via regulating the tight junction protein levels to regulate the integrity and function of BBB.…”
Section: Parametersmentioning
confidence: 59%
“…Besides, the link between inflammation and cancer, as well as the role CXCR4 plays in the transformation between the two sides, has drawn great attention of oncological researchers. Therefore, small molecular antagonists targeting CXCR4, such as BKT140, plerixafor and AMD3100, have been widely used in cancer treatment 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Moreover, binding of CXCL-12 to its receptor CXCR4 has been shown to induce tumor proliferation and cancer progression, and these effects were attenuated when this pathway was knocked down in pre-clinical in vivo models. 61 PDGFA is a potent activator for mesenchymal-origin cells, and stimulates chemotaxis, proliferation and angiogenesis in cancer, 62 engaging several pathways such as Ras-MAPK, PI3K, PLCÎł and inducing VEGF production. 62,63 Plasma CRP concentration is increased in response to inflammation, tissue damage and infection, and may promote tumor growth and metastasis by causing low-grade inflammation in breast cancer, although the exact pathogenesis is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…This would provide in vivo validation of eRNA function and describe pre-clinical models for future eRNA-targeted therapies. Indeed, the feasibility of targeting tissue-specific and disease-relevant enhancers using LNA or CRISPR-based strategies might have clinical importance [168,169].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%